Synthesis and Biological Evaluation of Termini-Modified and Cyclic Variants of the Connexin43 Inhibitor Peptide5 - Crystal Chan, Sin Hang; Griffin, Jarred M.; Clemett, Connor A.; Brimble, Margaret A.; O’Carroll, Simon J.; Harris, Paul W. R. (Frontiers in Chemistry, 2022)
Peptide5 is a 12–amino acid mimetic peptide that corresponds to a region of the extracellular loop 2 (EL2) of connexin43. Peptide5 regulates both cellular communication with the cytoplasm (hemichannels) and cell-to-cell communication (gap junctions), and both processes are implicated in neurological pathologies. To address the poor in vivo stability of native peptide5 and to improve its activity, twenty-five novel peptide5 mimetics were designed and synthesized. All the analogues underwent biological evaluation as a hemichannel blocker and as a gap junction disruptor, and several were assessed for stability in human serum. From this study, it was established that several acylations on the N-terminus were tolerated in the hemichannel assay. However, the replacement of the L-Lys with an N-methylated L-Lys to give H-VDCFLSRPTE-N-MeKT-OH showed good hemichannel and gap junction activity and was more stable in human serum. The cyclic peptide variants generally were not tolerated in either the hemichannel and gap junction assay although several possessed outstanding stability in human serum.